Instagram Influencers at the Crossroads between Publics and Communities - Caliandro, Alessandro; Gandini, Alessandro; Bainotti, Lucia; Anselmi, Guido (The Platformisation of Consumer Culture, 2024)
In this chapter, we map social formations emerging around influencers' accounts on Instagram. Influencers are key social actors shaping how consumption is organised in the digital society. To fully unpack their role, it is relevant to consider their practices at the crossroads between brand publics and communities. In light of this complexity, we ask: In which ways do brand publics and influencer communities coexist on Instagram? What is the relationship between these hybrid social formations and the platformisation of consumer culture? The chapter shows that the coexistence of features typical of both brand publics and communities around the influencer persona leads to the formation of hybrid influencer publics - social formations characterised by the coexistence of mediation and interaction, the emphasis on affective forms of communication, and the presence of a mediated form of identity.